2002
DOI: 10.1073/pnas.062186399
|View full text |Cite
|
Sign up to set email alerts
|

Benthic eukaryotic diversity in the Guaymas Basin hydrothermal vent environment

Abstract: Molecular microbial ecology studies have revealed remarkable prokaryotic diversity in extreme hydrothermal marine environments. There are no comparable reports of culture-independent surveys of eukaryotic life in warm, anoxic marine sediments. By using sequence comparisons of PCR-amplified small subunit ribosomal RNAs, we characterized eukaryotic diversity in hydrothermal vent environments of Guaymas Basin in the Gulf of California. Many sequences from these anoxic sediments and the overlaying seawater represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
337
4
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 343 publications
(365 citation statements)
references
References 25 publications
15
337
4
1
Order By: Relevance
“…To circumvent the requirement for laborious optimization and concurrent largescale culturing that is necessary to facilitate the complex and distinct growth requirements of eukaryotes from natural environments, culture-independent approaches are requisite to complete community diversity surveys (Edgcomb et al, 2002;Lepere et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…To circumvent the requirement for laborious optimization and concurrent largescale culturing that is necessary to facilitate the complex and distinct growth requirements of eukaryotes from natural environments, culture-independent approaches are requisite to complete community diversity surveys (Edgcomb et al, 2002;Lepere et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Such studies revealed considerable microbial diversity not captured by culture-dependent methods. With these new methods, it is possible to sample from a broader range of microbial habitats (Dawson & Pace 2002, Edgcomb et al 2002, Zettler et al 2002, Lopez-Garcia et al 2003, to sample previously undetected microbes (Diez et al 2001, Moon-van der Staay et al 2001, and to determine the spatial and temporal scales of microbial diversity (Romari & Vaulot 2004, Behnke et al 2006, Cordova-Kreylos et al 2006, Ley et al 2006. Although ciliates are often captured in studies of eukaryotic diversity, we know of no published reports focusing specifically on ciliate diversity using cultureindependent molecular methods.…”
mentioning
confidence: 99%
“…Environmental molecular surveys have revolutionized our understanding of microbial systems (6). Phylogenetic surveys also have been applied successfully to study the community composition of eukaryotic microbes at several deep-sea sites (7)(8)(9)(10)(11)(12)(13)(14)(15)(16); however, to date, no study has addressed the phylogenetic diversity of eukaryotic microbial life of one of the largest habitats, covering over half of the Earth's surface: the abyssal plains.…”
mentioning
confidence: 99%